2011
DOI: 10.1590/s0004-27492011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Achados oculares em crianças com toxoplasmose congênita

Abstract: RESUMOObjetivo: Conhecer as lesões oculares mais frequentes encontradas em crianças expostas à toxoplasmose congênita. Métodos: Trata-se de um estudo retrospectivo, a partir de uma coorte histórica, de abordagem quantitativa. Foram avaliadas crianças encaminhadas de um serviço de infectologia pediátrica e inseridas apenas aquelas com diagnóstico confirmado de toxoplasmose congênita. A avaliação oftalmológica incluiu o mapeamento de retina sequencial, sob dilatação pupilar. Resultados: Das 58 crianças presumive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Similar results were found in a previous study with a similar population, which identified microcephaly in 20.8%, intracranial calcification in 37.5% and chorioretinitis in 54% of the sample 20 . Screening for toxoplasmosis during pregnancy can anticipate the diagnosis so that treatment is performed at gestation, reducing the risk of injury to the NB 11,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in a previous study with a similar population, which identified microcephaly in 20.8%, intracranial calcification in 37.5% and chorioretinitis in 54% of the sample 20 . Screening for toxoplasmosis during pregnancy can anticipate the diagnosis so that treatment is performed at gestation, reducing the risk of injury to the NB 11,21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, when the infection occurs during the third trimester of gestation, the child may be born without evidence of the disease, and may present them years latter Health and Diversity, v.1, p.53-58, 2017(JONES et al, 2003SOUZA et al, 2010). The main manifestation observed in congenital toxoplasmosis is the toxoplasmic retinochoroiditis, being present in 80% of cases (SOARES et al, 2011). However, brain calcifications, mental retardation, hydrocephalus, with macro and microcephaly may also be present in patients who develop this condition (VIDIGAL et al, 2002).…”
Section: Congenital Toxoplasmosismentioning
confidence: 99%
“…As daily routine, the cleaning of catteries, with fecal material removal is indicated, since, in dependence on the environmental conditions, the T. gondii oocysts eliminated doi: 10.7243/2052-5958- [1][2][3][4][5][6][7] by cats require at least 24 hours to sporulate and become infectious. It is also important to cover or encircle sand tanks for children recreation, especially when they are not in use, to prevent the cats access [12,33].…”
Section: Control Of Human Toxoplasmosismentioning
confidence: 99%
“…Women in initial stages of gestation may undergo miscarriage, premature birth, neonatal death and even the classical Sabin's Triad, characterized by retinochoroiditis, cerebral calcifications, hydrocephaly or microcephaly [1,2].…”
Section: Introductionmentioning
confidence: 99%